Strategi Industrialisasi Hubungan Dengan Sektor Pertanian di Wilayah Sidoarjo - Angga Dwi Permadi; Durratul Hikmah Fatus Solikhah; Muhammad Yasin (Student Research Journal, 2023)
The industrialization strategy exists to respond to challenges that are in line with Indonesia's vision of becoming a sovereign, developed, just and prosperous country. Changes in a country's economy are interpreted as a process of structural transformation. Structural changes in the modern economy include changes in agricultural to non-agricultural activities, from industry to services, changes in the scale of productive units, and changes from individual companies to legal entities, as well as changes in the working status of workers. Analyzing the data in this study is a descriptive research method. The sources used come from literature collected through websites, journals, Central Statistics Agency various relevant sources. In the agricultural industry, it is very important to identify value-added activities that will support the necessary investments through research in the aspects of marketing and processing, application of biotechnology, design and restructuring of distribution systems.